Local Wisdom of Nggahi Rawi Pahu as a Pillar of Social Harmony in Dompu Regency - Enung Nurhasanah; Wayan Suja (International Journal of Educational and Life Sciences, 2024)
Local wisdom is a very important element in building and maintaining social harmony in various communities, including in Dompu Regency Nggahi Rawi Pahu is not just a philosophy, but a life guide that emphasizes honesty, justice, and responsibility. This study uses a qualitative approach with literature study methods and in-depth interviews. Data were obtained through local documents, participatory observations, and interviews with community leaders, traditional leaders, and academics in Dompu. The analysis was carried out thematically to explore the essence of Nggahi Rawi Pahu and how it is implemented. The results of the study revealed three main points. First, Nggahi Rawi Pahu is a culture of speech that emphasizes harmony between words and deeds. This culture has long been an important part of the lives of the Dompu community and continues to survive today. Second, Nggahi Rawi Pahu has a deep meaning for individuals, especially in forming a personality that reflects the values ​​of wisdom, religiosity, and leadership, both in the family and society.